2004
DOI: 10.1080/08880010490457051
|View full text |Cite
|
Sign up to set email alerts
|

IN VITRO DETERMINATION OF THE APOPTOTIC EFFECT OF HEPARIN ON LYMPHOBLASTS USING DNA ANALYSIS AND MEASUREMENTS OF Fas AND Bcl-2 PROTEINS BY FLOW CYTOMETRY

Abstract: Heparin has an apoptotic effect beside its anticoagulant, anti-inflammatory, antihypertensive, and antiproliferative effects. In this study, the authors detected the percentages of apoptotic lymphoblasts and the expressions of apoptotic Fas protein and antiapoptotic Bcl-2 protein with flow cytometry in vitro after the incubation of lymphoblasts with heparin. Eleven newly diagnosed acute lymphoblastic leukemia (ALL) children were included in the study. Lymphoblasts were incubated in all different levels of hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 27 publications
3
14
0
Order By: Relevance
“…We demonstrated in this study that the greatest proliferation effect of heparin and the highest SPF ratio were determined in 20 U/ml concentration at 1 h. Recent studies from Erduran et al [30] determined that the greatest apoptotic effect of heparin on the lymphoblasts was detected in 20 U/ml concentration at 1 h. The results of some recent studies were found to be concordant [28][29][30]. Apoptosis and proliferation are important regulators of normal development and homeostasis in the bone marrow.…”
Section: Aksoy Et Al Heparin and Human B-lymphoblast Cell Cyclesupporting
confidence: 66%
See 1 more Smart Citation
“…We demonstrated in this study that the greatest proliferation effect of heparin and the highest SPF ratio were determined in 20 U/ml concentration at 1 h. Recent studies from Erduran et al [30] determined that the greatest apoptotic effect of heparin on the lymphoblasts was detected in 20 U/ml concentration at 1 h. The results of some recent studies were found to be concordant [28][29][30]. Apoptosis and proliferation are important regulators of normal development and homeostasis in the bone marrow.…”
Section: Aksoy Et Al Heparin and Human B-lymphoblast Cell Cyclesupporting
confidence: 66%
“…On the other hand, heparin causes apoptosis in human peripheral blood neutrophils, lymphoblasts and mononuclear cells, and indicates its apoptotic effect on lymphoblasts via extrinsic or intrinsic pathways [27][28][29]. We demonstrated in this study that the greatest proliferation effect of heparin and the highest SPF ratio were determined in 20 U/ml concentration at 1 h. Recent studies from Erduran et al [30] determined that the greatest apoptotic effect of heparin on the lymphoblasts was detected in 20 U/ml concentration at 1 h. The results of some recent studies were found to be concordant [28][29][30].…”
Section: Aksoy Et Al Heparin and Human B-lymphoblast Cell Cyclementioning
confidence: 99%
“…In our evaluation of the influence of heparin on tumor cell proliferation, cell cycle and apoptosis, we found that it could inhibit proliferation of PC-3M tumor cells and arrest them in the G 0 /G 1 phase. Heparin has been reported to induce apoptosis in tumor cells mediated by caspase-3, caspase-8, Fas, and Bcl-2 [15] . In this study, we did not find a significant influence of heparin on tumor cell apoptosis, although there was a slight increase in number of apoptotic PC-3M cells treated with heparin (125 μg/mL).…”
Section: Effect Of Heparin On Brdu Incorporation and Ki67 Expression mentioning
confidence: 99%
“…Beside its anticoagulant, anti-inflammatory, antihypertensive and antiproliferative effects [1][2][3], heparin has the apoptotic effect in lymphoblasts, in vitro [4][5][6]. Manaster et al [7] claimed that 50, 100 and 200 U/ml concentrations of heparin induce apoptosis in human peripheral blood neutrophils, in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Manaster et al [7] claimed that 50, 100 and 200 U/ml concentrations of heparin induce apoptosis in human peripheral blood neutrophils, in vitro. In our studies, lymphoblasts were incubated with 0, 5, 10 and 20 U/ml concentrations of heparin at 0, 1 and 2 hours and the highest apoptosis was determined in 20 U/ml heparin concentration at first hour [4][5][6]. The expression of fas, the activities of caspase-3 and -8 increased and the expression of bcl-2 decreased when lymphoblasts were incubated with heparin in 10 and 20 U/ml concentrations at 1 and 2 hours.…”
Section: Introductionmentioning
confidence: 99%